Analysis of Flood Control Plan in Cibitung Kertagraha Housing, Bekasi District - Acep Hidayat; Siti Nur Azizah (Journal of World Conference (JWC), 2021)
The change in the function of land to housing can cause a decrease in the level of the water absorption zone that occurs in the area and can cause inundation or even flooding. Housing can be categorized as good, that is, it must have drainage facilities that can drain rainwater quickly and not cause stagnation of water even though the rainfall is very high. Therefore, the right solution to tackle standing water, drainage problems, and flooding in Kertagraha housing is to create a retention pond because in the kertagraha housing there is no final storage system that is suitable for dealing with flooding,The location of this research is located in Sukarukun Village, Sukatani District, Cibitung, Bekasi Regency with the category of housing area. In this study, a hydrological analysis was carried out with rainfall data from the Rain Post Station located in Sukatani and the TRMM Rain Post located in Cikarang within a 10-year return period starting from 2010-2019, and the planned flood discharge data were obtained. Furthermore, hydraulic analysis is carried out to determine the flood discharge capacity in the existing drainage channels and to plan the volume of the storage pool. After that, the retention pond design planning is carried out.In the calculation analysis, it is found that the planned rain discharge value in the next 10 years is 7.393 m³ / second using the Haspers method. The total capacity of the storage pool is 12,385 m³, with the dimensions of the retention pond, namely P = 70m, L = 20m, T = 10meter. With a concentration time of 1675 seconds. Based on the analysis carried out and there is sufficient land, this retention pond is the best solution to overcome the flood problem in Kertagraha housing.